IMPORTANCE OF THE MOTIVATIONAL FACTORS: EMPIRICAL ANALYSIS OF STUDENTS AND EMPLOYEES - Eftimov, Lјupcho; Ristovska Andrijana (CEA Center for Economic Analyses, 2016)
The degree of the workforce motivation is crucial for organizations in achieving organizational goals. But what are the most important factors that motivate employees? In this respect, compared with the theoretical postulates of the theories of motivation, this paper conducted a survey designed to determine the motivational factors that the students of the last academic year of study as future employees have recognized as influential for better work performance and to assess whether the factors change by changing the environment and the employment status by determining the motivational factors that improve the work performance recognized by the current employees with different demographic characteristics.
Keywords: workforce motivation, theories of motivation, motivational factors, work performance, students, employees